BALABOLKA Software to Improve the Ability to Access Electronic Learning Resources for Visual Impairment Students - Dirham Gumawang Andipurnama; Dikdik Mantera Wiguna; Budi Susetyo; Ranti Novianti (Journal of ICSAR, 2022)
This research was aimed to discover the use of Balabolka software in improving the ability to access electronic learning resources for visual impairment students who face the difficulties in accessing electronic learningresources. Assistive technology is needed to access these electronic learning resources. The quantitative approach to the Single Subject Research (SSR) method of A-B-A design was conveyed in order to collect the data. Based on the results, the baseline phase level 1 (A1) was obtained in RF subject of 54.60 percent. Mean intervention phase level (B) in RF subject was 75.64 percent. Mean baseline phase level 2 (A2) in RF subject by 81.9 percent. The findings showed that the use of Balabolka software to be helpful in supporting the ability to access electronic learning resources because Balabolka software offered audio functions to get information from computer devices.